PERFORMANCE AND INCOME INEQUALITY AMONG SELECTED RICE VALUE-CHAIN ACTORS IN QUA’AN PAN LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Folorunso, Solomon T.; Ademiluyi, Ibiyinka O.; Omosebi, Tayo; Adeniyi, Olufunso O. (FUDMA JOURNAL OF SCIENCES, 2025)
Empirical evidence in Nigeria indicate that investors have not explored the investment opportunities in rice production because they are unaware of the performance of rice value-chain actors, local rice production has not matched demand, and rice farmers’ productivity have not significantly improved. The study was carried out in Qua’an Pan Local Government Area Plateau State, Nigeria. A Multistage sampling technique was used to select 106 farmers; 83 marketers and 50 rice millers; Primary data was collected through the administration of a well–structured questionnaire. Net Income model, Gini-coefficient and Lorenz curve was used for the study. The result reveals average total ravenue, TVC and TFC per production cycle along the value chain were N509,681.10, N46,187.50 and N273,000.00; N157,664.55, N23,353.00 and N113,340.00 for farmers, marketers and processors and N61, 503.94 and N10,758.25 for farmers and processors while the average TC for the value chain actors were N219,168.59, N34,111.25 and N159,660.00. The values of the NI and ROI were N290,512.69, N12,076.25 and N138,394.71 and 1.33, 1.12 and 1.03 respectively. The pattern of income distribution of value chain actors indicates the concentration of rice value chain actors’ income in the hands of a few. The following recommendations are proffered: Urgent policy reforms are required to achieve the redistribution of income among value chain actors, production inputs for farmers be subsidized, marketing infrastructures be upscaled, processing facilities be duty free.